SURVEY OF THE EFFECTIVENESS OF THE FREE NUTRITIONAL MEAL PROGRAM (MBG) FOR STUDENTS AT MUHAMMADIYAH HEALTH VOCATIONAL SCHOOL, KOTA JUANG DISTRICT, BIREUEN REGENCY YEAR 2025 - Sri Wahyuni; Aris Winandar; Rini Fitriani; Fatin Ulfia; Nadia Humaira; Ira Azzuhra (STMIK Indonesia Banda Aceh, 2026)
The Free Nutritious Meal Program (MBG) is a crucial intervention to improve students' nutritional status through the provision of balanced meals. It aims to create a school environment that supports optimal growth and development and serves as a preventative measure against the risks of malnutrition, such as anemia and chronic energy deficiency. This study aimed to determine student satisfaction with the implementation of the MBG Program at Muhammadiyah Health Vocational School in Bireuen . This study used a quantitative descriptive method, with 60 students drawn from a stratified random sampling method ( 30 grade X students and 30 grade 1 XI students) from a total population of 145 students. Survey results indicated that the MBG Program was positively received and strongly supported by respondents. High levels of satisfaction were observed, with the majority of respondents satisfied with the quality and nutrition of the food (66.7%) and the overall implementation of the program (73.3%). The program also generated direct benefits, with 66.7% of respondents experiencing positive impacts on health and learning. However, significant gaps remain; 53.3% of respondents did not experience benefits across the social, psychological, and economic dimensions, indicating the need for more comprehensive interventions to maximize its multidimensional impact.